In Vitro Effect of Copper (I) Complex [Cu(Nn1)2](Clo4) on Vibrio Harveyi bb170 Biofilm Formation - Guerrero-Nunez, J; Guerrero-Nunez, J; Modak-Canobra, B; Aldabaldetrecu-Urbieta, M; Aldabaldetrecu-Urbieta, M; Parra-Mardonez, N (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Biofilm formation in pathogenic bacteria is an important factor of resistance to antimicro-bial treatments, allowing them to survive for a long time in their hosts. In the search for new antibi-ofilm agents, in this work we report the activity of a copper (I) complex, [Cu(NN1)2]ClO4, synthe-sized with Cu (I) and NN1, an imine ligand 6-((quinolin-2-ylmethylene)amino)-2H-chromen-2-one, a derivate of natural compound coumarin. The antibacterial and antibiofilm capacity was evaluated in Vibrio harveyi BB170 used as model bacteria. Antibacterial activity was measured in vitro by minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC) and half-maximal inhibitory concentration (IC50) determination. Antibiofilm capacity of copper (I) complex was ana-lyzed by different concentrations of IC50 values. The results showed that the sub-IC50 concentration, 12.6 µg/mL of the copper (I) complex, was able to reduce biofilm formation by more than 75%, and bacterial viability was reduced by 50%. Inverted and confocal laser scanning microscopy showed that the [Cu(NN1)2]ClO4 complex affected the biofilm structure. Therefore, the copper (I) complex is effective as an antibiofilm compound in V. harveyi BB170. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.